How Do I Model State? Let Me Count the Ways. - FOSTER, IAN; PARASTATIDIS, SAVAS; WATSON, PAUL; MCKEOWN, MARK (Communications of the ACM, 2008)
The article discusses how a computer programmer is able to model state, examining the manner in which one defines interactions among Web services to support operations on state. Topics include data values, operations that depend on prior operations, and persisting across interactions. The authors attempt to provide various approaches to modeling state. An example of such a program would be an airline reservation system, the article states. Also discussed is whether the state is complex or simple and multiple distinct processes on back-end computers.